2015
DOI: 10.1890/es15-00098.1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the linkage between shrub encroachment and recent greening in water‐limited southern Africa

Abstract: Abstract. There have been reports of widespread increases in satellite-derived vegetation indices in drylands across the globe. At the same time, there are numerous field-based observations of increases in the density of small woody plant species, a process known as shrub encroachment. We compare groundbased observations of shrub encroachment with information from 14 years of Tropical Rainfall Measuring Mission (TRMM) precipitation data, Moderate Resolution Imaging Spectroradiometer (MODIS) Normalized Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 77 publications
(99 reference statements)
2
26
0
Order By: Relevance
“…Increasing vegetation productivity can also relate to bush encroachment which characterizes the invasion of alien species and especially the expansion of woody vegetation in areas where it is not naturally occurring [75,76]. This invasive vegetation suppresses palatable plant species and grasslands [76][77][78]. Bush encroachment is an ongoing problem in South Arica and in Eastern Cape Province [79,80] and could be one possible explanation for the depicted increasing trends mainly in communal land, where bush encroachment is an indicator of prevalent land degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing vegetation productivity can also relate to bush encroachment which characterizes the invasion of alien species and especially the expansion of woody vegetation in areas where it is not naturally occurring [75,76]. This invasive vegetation suppresses palatable plant species and grasslands [76][77][78]. Bush encroachment is an ongoing problem in South Arica and in Eastern Cape Province [79,80] and could be one possible explanation for the depicted increasing trends mainly in communal land, where bush encroachment is an indicator of prevalent land degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the VOD wood shows much larger areas of positive trends as compared to VOD leaf (Fig. 4), indicating a potential underestimation of the spatial extent of shrub encroachment based on optical remote sensing data in this region (Saha et al, 2015). Manmade fires are used for controlling bush encroachment in Botswana and Zimbabwe (Gandiwa, 2011;Mudongo et al, 2016).…”
Section: Interpretation Of Changes In Subcontinental Hot Spot Regionsmentioning
confidence: 99%
“…However, trends in NDVI do not necessarily reflect changes in other vegetation characteristics, such as physiognomic structure and water content. Some research has suggested that NDVI can be used to estimate woody vegetation cover in savanna and woodland ecosystems [26,27], and that positive trends in NDVI can be interpreted as woody vegetation encroachment or densification [28,29]. In contrast, Mitchard and Flintrop [30] pointed out that the signals in the NDVI were more related to changes in the grass layer than woody vegetation cover in West Africa.…”
Section: Introductionmentioning
confidence: 99%